The use of the additional field player on handball: analysis of the Rio 2016 Olympic Games - Krahenbühl, T.; Pessoa de Souza, N.; Leonardo, L.; Galatti, L. R.; De Conti Teixeira Costa, G. (Revista Internacional de Ciencias del Deporte, 2019)
This study aims at analyzing the effectiveness of using an additional field player, when goalkeeper is replaced, during the positional attack in the case of numerical equality, superiority or inferiority and when counterattacks are suffered. The sample consisted of 841 attack actions collected from eight games of men`s teams in the knockout phase of the Rio 2016 Olympic Games. The number of goals scored and the counterattacks suffered in symmetrical and asymmetrical situations were checked for both situations: using the additional player or not. Was performed the chi-square test and the effect power was calculated using Phi. The analysis of the attack showed that there was no association between goal-making and the use of the additional field player in different asymmetric situations. There was no association between the reach of the goal in case of opponent`s counterattack substitution of the goalkeeper with the additional field player or not as well as no association between punishment and goal achievement in different offensive situations. The use of an additional field player did not benefit the team in attack actions and brought no disadvantages in the scoreboard. These results show that, in this championship, such strategy did not produce significant changes in decisive games of men`s handball.